Lnc-PSMA8-1 activated by GEFT promotes rhabdomyosarcoma progression via upregulation of mTOR expression by sponging miR-144-3p - Lian Meng; Hao Shang; Qianqian Liu; Zhenzhen Li; Xiaomeng Wang; Qianru Li; Feng Li; Zhenguo Zhao; Chunxia Liu (BMC Cancer, 2024)
Abstract Background GEFT is a key regulator of tumorigenesis in rhabdomyosarcoma (RMS), and overexpression of GEFT is significantly correlated with distant metastasis, lymph node metastasis, and a poor prognosis, yet the underlying molecular mechanism is still poorly understood. This study aimed to investigate and validate the molecular mechanism of GEFT-activated lncRNAs in regulating mTOR expression to promote the progression of RMS. Methods GEFT-regulated lncRNAs were identified through microarray analysis. The effects of GEFT-regulated lncRNAs on the proliferation, apoptosis, invasion, and migration of RMS cells were confirmed through cell functional experiments. The target miRNAs of GEFT-activated lncRNAs in the regulation of mTOR expression were predicted by bioinformatics analysis combined with quantitative real-time polymerase chain reaction (qRT–PCR) analysis. The expression of lnc-PSMA8-1, miR-144-3p, and mTOR was measured by qRT–PCR in RMS tissue samples and cell lines. The regulatory mechanisms of the lnc-PSMA8-1-miR-144-3p-mTOR signaling axis were verified by RNA-binding protein immunoprecipitation (RIP), a luciferase reporter assay, qRT–PCR analysis, Western blot analysis, and cell functional experiments. Results The microarray-based analysis identified 31 differentially expressed lncRNAs (fold change > 2.0, P < 0.05). Silencing the 4 upregulated lncRNAs (lnc-CEACAM19-1, lnc-VWCE-2, lnc-GPX7-1, and lnc-PSMA8-1) and overexpressing the downregulated lnc-FAM59A-1 inhibited the proliferation, invasion, and migration and induced the apoptosis of RMS cells. Among the factors analyzed, the expression of lnc-PSMA8-1, miR-144-3p, and mTOR in RMS tissue samples and cells was consistent with the correlations among their expression indicated by the lncRNA–miRNA–mRNA regulatory network based on the ceRNA hypothesis. lnc-PSMA8-1 promoted RMS progression by competitively binding to miR-144-3p to regulate mTOR expression. Conclusion Our research demonstrated that lnc-PSMA8-1 was activated by GEFT and that the former positively regulated mTOR expression by sponging miR-144-3p to promote the progression of RMS. Therefore, targeting this network may constitute a potential therapeutic approach for the management of RMS.